Multicenter study of pediatric Epstein‐Barr virus–negative monomorphic post solid organ transplant lymphoproliferative disorders. Issue 5 (26th December 2022) - Afify, Zeinab A. M.; Taj, Mary M.; Orjuela‐Grimm, Manuela; Srivatsa, Kavitha; Miller, Tamara P.; Edington, Holly J.; Dalal, Mansi; Robles, Joanna; Ford, James B.; Ehrhardt, Matthew J.; Ureda, Tonya J.; Rubinstein, Jeremy D.; et al.
Abstract: Background: Pediatric Epstein‐Barr virus–negative monomorphic post solid organ transplant lymphoproliferative disorder [EBV(−)M‐PTLD] comprises approximately 10% of M‐PTLD. No large multi‐institutional pediatric‐specific reports on treatment and outcome are available. Methods: A multi‐institutional retrospective review of solid organ recipients diagnosed with EBV(−)M‐PTLD aged ≤21 years between 2001 and 2020 in 12 centers in the United States and United Kingdom was performed, including demographics, staging, treatment, and outcomes data. Results: Thirty‐six patients were identified with EBV(−)M‐PTLD. Twenty‐three (63.9%) were male. Median age (range) at transplantation, diagnosis of EBV(−)M‐PTLD, and interval from transplant to PTLD were 2.2 years (0.1–17), 14 years (3.0–20), and 8.5 years (0.6–18.3), respectively. Kidney ( n  = 17 [47.2%]) and heart ( n  = 13 [36.1%]) were the most commonly transplanted organs. Most were Murphy stage III ( n  = 25 [69.4%]). Lactate dehydrogenase was elevated in 22/34 (64.7%) and ≥2 times upper limit of normal in 11/34 (32.4%). Pathological diagnoses included diffuse large B‐cell lymphoma ( n  = 31 [86.1%]) and B–non‐Hodgkin lymphoma (B‐NHL) not otherwise specified (NOS) ( n  = 5 [13.9%]). Of nine different regimens used, the most common were: pediatric mature B–NHL‐specific regimen ( n  = 13 [36.1%]) and low‐dose cyclophosphamide, prednisone, and rituximab ( n  = 9 [25%]). Median follow‐up from diagnosis was 3.0 years (0.3–11.0 years). Three‐year event‐free survival (EFS) and overall survival (OS) were 64.8% and 79.9%, respectively. Of the seven deaths, six were from progressive disease. Conclusions: EFS and OS were comparable to pediatric EBV(+) PTLD, but inferior to mature B‐NHL in immunocompetent pediatric patients. The wide range of therapeutic regimens used directs our work toward developing an active multi‐institutional registry to design prospective studies. Plain Language Summary: Pediatric Epstein‐Barr virus–negative monomorphic post solid organ transplant lymphoproliferative disorders (EBV(−)M‐PTLD) have comparable outcomes to EBV(+) PTLD, but are inferior to diffuse large B‐cell lymphoma in immunocompetent pediatric patients. The variety of treatment regimens used highlights the need to develop a pediatric PTLD registry to prospectively evaluate outcomes. The impact of treatment regimen on relapse risk could not be assessed because of small numbers. In the intensive pediatric B–non‐Hodgkin lymphoma chemoimmunotherapy group, 11 of 13 patients remain alive in complete remission after 0.6 to 11 years. Abstract : No consensus exists about treatment and outcomes of pediatric Epstein‐Barr virus–negative monomorphic post solid organ transplant lymphoproliferative disorder [EBV(−)M‐PTLD]. Retrospective evidence suggests that EBV(−)M‐PTLD has comparable outcomes to published results in EBV(+) PTLD, but inferior to diffuse large B‐cell lymphoma in immunocompetent pediatric patients.